Deficiência e interseccionalidade: culturas, políticas e práticas educacionais em debate - Carlo Schmidt; Eliana da Costa Pereira de Menezes; Clenio Perlin Berni; Mônica Pereira dos Santos; Jacqueline de Souza Gomes; Laura Ceretta Moreira (Universidade Federal de Santa Maria (UFSM), 2021)
Editorial